The Impact of Service Quality and Service Loyalty on the Users Satisfaction at PT. Adhigana Pratama Mulya Batam - Nazarwin Nazarwin; Riki Wanda Putra; Adhi Pratistha Silen; Markus Asta Patma Nugraha; M. Fitriansyah Aldebaran; Muhammad Rizky Prima Sakti (FOUNDAE (Foundation of Advanced Education), 2025)
In an increasingly competitive service industry, understanding the determinants of user satisfaction is essential for organizational growth and customer retention. This study aims to examine the effects of service quality and service loyalty on user satisfaction at PT. Adhigana Pratama Mulya Batam. Employing a quantitative ex-post facto design, data were collected through questionnaires distributed to 200 respondents, consisting of ship crew members as direct users of the company’s services. The data were analyzed using multiple linear regression with the SPSS application. The results reveal that both service quality (t(197) = 4.419 > 1.984, p < 0.001) and service loyalty (t(197) = 9.957 > 1.984, p < 0.001) have significant positive effects on user satisfaction, while their combined influence is also statistically significant (F(2, 197) = 96.379 > 3.00, p < 0.001). These findings indicate that higher levels of service quality and employee loyalty lead to greater user satisfaction. The study suggests that the company should strengthen employee training, enhance user engagement, and continuously improve global service standards. Future research should incorporate additional factors such as infrastructure, technological facilities, pricing competitiveness, and brand image to obtain a more comprehensive understanding of user satisfaction